2021
DOI: 10.3389/fmed.2021.607059
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences on Clinical Characteristics, Severity, and Mortality in Adult Patients With COVID-19: A Multicentre Retrospective Study

Abstract: Background: Coronavirus disease-2019 (COVID-19) epidemic is spreading globally. Sex differences in the severity and mortality of COVID-19 emerged. This study aims to describe the impact of sex on outcomes in COVOD-19 with a special focus on the effect of estrogen.Methods: We performed a retrospective cohort study which included 413 patients (230 males and 183 females) with COVID-19 from three designated hospitals in China with a follow up time from January 31, 2020, to April 17, 2020. Women over 55 were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 43 publications
7
50
2
1
Order By: Relevance
“…This feature has been documented worldwide because a male bias in COVID-19 mortality was reported in the 37 out of the 38 countries that have provided sex disaggregated data [8]. Other studies have also reported that a higher proportion of men were hospitalized than females [17,23]. Our data showed that this is not the case for younger (< 45 years) and older patients (> 75 years), in whom the hospitalizations of females and males were similar.…”
Section: Discussionsupporting
confidence: 55%
“…This feature has been documented worldwide because a male bias in COVID-19 mortality was reported in the 37 out of the 38 countries that have provided sex disaggregated data [8]. Other studies have also reported that a higher proportion of men were hospitalized than females [17,23]. Our data showed that this is not the case for younger (< 45 years) and older patients (> 75 years), in whom the hospitalizations of females and males were similar.…”
Section: Discussionsupporting
confidence: 55%
“…However, there was no significant difference in disease severity and mortality between postmenopausal and premenopausal females after eliminating the confounding of age in this study. A retrospective study in patients with COVID-19 in China also reported that estrogen might not be directly related to the lower mortality in females (Sha et al, 2021). Due to the small sample size after PSM, large sample investigations are still needed to verify this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has been reported to play a crucial role in disease outcomes in COVID-19 patients, attributed to its ability to reduce inflammatory IL-6, IL-8 and TNF-a levels (Alwani et al, 2021). However, this conclusion is not consistent (Alwani et al, 2021;Sha et al, 2021). This study aimed to provide information on differences in clinical characteristics and outcomes between male and female patients and explore the effect of estrogen on disease outcomes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(7) A metaanalysis of 58 studies showed men with a 1.57-fold higher odds ratio for mortality and a 1.65-fold higher for severe infection than women (8). Recently Sha et al confirmed again that mortality of women is lower than in men but noticed no-difference in inhospital mortality in women < 55 years of age compared with the same age men (9). Beside several limitations of this study like retrospective, exploratory, no measurement of oestrogen level and no information of the history of hormone therapy, they opened the discussion whether an association of oestradiol and mortality in COVID-19 disease exists.…”
Section: Epidemiology-sars-cov-2 Infection and Covid-19 Mortalitymentioning
confidence: 99%